Computed Tomography virtual lab software application in process tomography research - Zulkarnay, Zakaria; Mohd. Hafiz, Fazalul Rahiman; Ruzairi, Abdul Rahim (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.